Randomised controlled trials of non-pharmacological interventions to improve patient-reported outcomes of colonoscopy: a scoping review - Sue-Chue-Lam, Colin; Castelo, Matthew; Benmessaoud, Amina; Kishibe, Teruko; Llovet, Diego; Brezden-Masley, Christine; Yu, Amy Yx; Tinmouth, Jill; Baxter, Nancy N (BMJ Open Gastroenterology, 2023)
Background and aims Non-pharmacological interventions to improve patient-reported outcomes of colonoscopy may be effective at mitigating negative experiences and perceptions of the procedure, but research to characterise the extent and features of studies of these interventions is limited. Methods We conducted a scoping review searching multiple databases for peer-reviewed publications of randomised controlled trials conducted in adults investigating a non-pharmacological intervention to improve patient-reported outcomes of colonoscopy. Study characteristics were tabulated and summarised narratively and graphically. Results We screened 5939 citations and 962 full texts, and included 245 publications from 39 countries published between 1992 and 2022. Of these, 80.8% were full publications and 19.2% were abstracts. Of the 41.9% of studies reporting funding sources, 11.4% were unfunded. The most common interventions were carbon dioxide and/or water insufflation methods (33.9%), complementary and alternative medicines (eg, acupuncture) (20.0%), and colonoscope technology (eg, magnetic scope guide) (21.6%). Pain was as an outcome across 82.0% of studies. Studies most often used a patient-reported outcome examining patient experience during the procedure (60.0%), but 42.9% of studies included an outcome without specifying the time that the patient experienced the outcome. Most intraprocedural patient-reported outcomes were measured retrospectively rather than contemporaneously, although studies varied in terms of when outcomes were assessed. Conclusion Research on non-pharmacological interventions to improve patient-reported outcomes of colonoscopy is unevenly distributed across types of intervention and features high variation in study design and reporting, in particular around outcomes. Future research efforts into non-pharmacological interventions to improve patient-reported outcomes of colonoscopy should be directed at underinvestigated interventions and developing consensus-based guidelines for study design, with particular attention to how and when outcomes are experienced and measured. PROSPERO registration number 42020173906.